Manejo laparoscópico para el síndrome de Wilkie (2019)
Introduction: Wilkie’s syndrome is a rare entity that presents as a chronic intestinal obstruction secondary to mechanical compression of the third portion of the duodenum due to a decreased aorto-mesenteric angle. This entity has a reported incidence of 0.012 to 2.4% and can lead to high morbidity and mortality; In addition, there are major controversies regarding its diagnosis and treatment, which is why the authors present a case report of a patient with a diagnosis of Wilkie's syndrome and its surgical management via laparoscopy. Methods: A case of a patient with clinical and imaging manifestations of superior mesenteric artery syndrome is presented, along with acritical review of the literature, taking into account articles published in the PubMed and ScienceDirect databases during the past 8 years. Clinical case: A 27-year-old patient with 20 years of abdominal pain that exacerbated one week before admission, with a clinical and imaging manifestations of Wilkie’s syndrome. Patient presents refractoriness to medical management, which led to a surgical approach with laparoscopic duodenum-jejunostomy that was carried out without perioperative complications and satisfactory results. Discussion and conclusions: The superior mesenteric artery syndrome is a rare entity that in some scenarios requires surgical management. The laparoscopic duodeno-jejunostomy is the procedure of choice to manage this entity as evidenced in our case, which is also consistent with what is reported in the world medical literature.